2008
DOI: 10.1055/s-2008-1027417
|View full text |Cite
|
Sign up to set email alerts
|

Zeigen Patienten aufgrund ihres Gesichtsfeldausfalls Veränderungen in ihrer Persönlichkeit? Eine Untersuchung mittels FPI-R und NEI-VFQ

Abstract: Contrary to our presumptions, patients with visual field defects did not show any changes in their personality. It is supposed that they have learned to compensate for their reduced visual functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…While quality of life estimates (both health-related and vision-related) were severely reduced in the investigated first stroke sample, Jobke et al reported that no change in personality features could be observed in patients with visual field loss in general [36]. …”
Section: Discussionmentioning
confidence: 99%
“…While quality of life estimates (both health-related and vision-related) were severely reduced in the investigated first stroke sample, Jobke et al reported that no change in personality features could be observed in patients with visual field loss in general [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, a deeper investigation of clinical manifestations not only of anxiety appears to be necessary in future large-scale studies. Additionally, personality changes after cerebral visual injury have been already reported (Jobke et al, 2008 ). For future studies, the combined use of the BSI or the long-version SCL-90 together with a personality inventory should be considered and diagnoses of mental disorders should be made available, which requires a more extensive study.…”
Section: Discussionmentioning
confidence: 83%